Ethical acceptability of research on human-animal chimeric embryos: summary of opinions by the Japanese Expert Panel on Bioethics - Mizuno, Hiroshi (Life Sci Soc Policy, 2015)
Human-animal chimeric embryos are embryos obtained by introducing human cells into a non-human animal embryo. It is envisaged that the application of human-animal chimeric embryos may make possible many useful research projects including producing three-dimensional human organs in animals and verification of the pluripotency of human ES cells or iPS cells in vivo. The use of human-animal chimeric embryos, however, raises several ethical and moral concerns. The most fundamental one is that human-animal chimeric embryos possess the potential to develop into organisms containing human-derived tissue, which may lead to infringing upon the identity of the human species, and thus impairing human dignity. The Japanese Expert Panel on Bioethics in the Cabinet Office carefully considered the scientific significance and ethical acceptability of the issue and released its “Opinions regarding the handling of research using human-animal chimeric embryos”. The Panel proposed a framework of case-by-case review, and suggested that the following points must be carefully reviewed from the perspective of ethical acceptability: (a) Types of animal embryos and types of animals receiving embryo transfers, particularly in dealing with non-human primates; (b) Types of human cells and organs intended for production, particularly in dealing with human nerve or germ cells; and (c) Extent of the period required for post-transfer studies. The scientific knowledge that can be gained from transfer into an animal uterus and from the production of an individual must be clarified to avoid unnecessary generation of chimeric animals. The time is ripe for the scientific community and governments to start discussing the ethical issues for establishing a global consensus.